Design of a nanocomposite with gold nanoparticles as the core and casein-templated gold nanoclusters as the shell with ultra-low protein corona for enhanced photodynamic therapy. Issue 23 (4th October 2022) - Zhang, Yue; Huang, Yuan; Chen, Hao; Luo, Xinxin; Zhang, Jinzhi; Wang, Hangxing; Zou, Qichao; Wang, Suxiao
Abstract : The photodynamic therapy efficiency of AuNPs-CS-AuNCs can be well enhanced by the synergy effect of CS-AuNCs and AuNPs which is due to the surface plasmonic amplification and energy transfer from AuNPs to AuNCs. Abstract : Gold nanoclusters (AuNCs) are well known in biosensing, bio-imaging and drug delivery areas, and they can sensitize the formation of singlet oxygen upon photoexcitation. However, designing AuNCs with a size bigger than 10 nm and in the meantime maintaining the fluorescence property, photodynamic function and long blood circulation time will be a big challenge. Herein, we design a gold nanocomposite with gold nanoparticles as the core and casein-templated gold nanoclusters as the shell (AuNPs-CS-AuNCs), having high photodynamic therapy efficiency and ultra-low protein corona properties as demonstrated by in vitro and in vivo experiments. The protein casein was used as an AuNC preparation template, reducing agent and also as an antifouling agent and their ultra-low protein corona properties are better than those of conventional PEGylated or BSA-coated nanocomposites. The photodynamic therapy efficiency of AuNPs-CS-AuNCs can be well enhanced by the synergy effect of CS-AuNCs and AuNPs which is due to the surface plasmonic amplification and energy transfer from AuNPs in the core to neighboring AuNCs on the shell for enhanced reactive oxygen species formation. Moreover, the size of our gold nanocomposites, around 31 nm, is bigger than that of conventional AuNCs, facilitating cell membrane crossing. The AuNPs-CS-AuNCs we designed can be potentially used as an anti-cancer therapy agent with excellent antifouling properties and high photodynamic therapy efficiency.